Removal of heavy metals by polymers from wastewater in the industry: A molecular dynamics approach - Le, Quynh Hoang; Smida, Kamel; Abdelmalek, Zahra; Tlili, Iskander (Engineering analysis with boundary elements, 2023)
One of the major pollutants of industrial water is lead metal, which causes widespread pollution in nature due to its wide use. Removing this pollutant, before the surface or subsurface disposal of wastewater, is a very effective measure in preserving and preventing the pollution of natural resources and the environment. Since surface adsorption is one of the effective methods for removing waste materials from wastewater. This study utilized molecular dynamics simulation to investigate the interactions between lead and polypropylene (PP). PP has proven to be the most effective substance for eliminating lead from aquatic environments. Given the presence of heavy metals such as lead (Pb), cadmium (Cd), mercury (Hg), chromium (Cr), zinc (Zn), and nickel (Ni) in aquatic ecosystems, it becomes crucial to remove lead from the wastewater generated by the oil and petrochemical industries. The findings of this research have the potential to assist in the removal of lead from industrial wastewater settings.